INTERGENERATIONAL DIFFERENCES OF FAMILY FIRMS IN INDONESIA: FINANCIAL STRUCTURE AND PERFORMANCE - Darmawan, Baziedy Aditya (Benefit: Jurnal Manajemen dan Bisnis, 2019)
This study aims to investigates the differences between the first, second, and third generation in managing the family firms as reflected by their financial structure and performance. All family firms listed IDX were used as the sample. There are 51 family firms, henceforth, classified as the first, second, and third generation of family business. One-Way ANOVA was performed to test the differences of short-term debt, long-term debt, retained earnings, family ownership, and performance (ROA) among family firms managed by the first, second, and third generation.The results of this study revealed that there are significant differences in term of short-term debt, long-term debt, retained earnings, and performance among family firms that managed by the first, second, and third generation. However, there?s no significant differences were found in term of family ownership among family firms managed by the first, second, and third generation. The differences of short-term debt and long-term debt shows decreased pattern. Whereas the differences of retained earnings, family ownership, and performance shows increase pattern. This findings are consistent with the pecking order theory in the firm?s life stage.